Pengaruh Kegiatan SLPHT Terhadap Pendapatan Usaha Tani Padi - Samsul Eksan (Corolla: Jurnal Sains Pertanian, 2015)
The purpose of this study was to determine the effect on revenue SLPHT rice farming and changes in farmer behavior, patterns of thinking, either individually or in groups in the pest control. To analyze the hypothesis of the existence of differences in earnings at each planting method, calculation of costs, revenue and income. To analyze how total costs and income earned, the calculation was conducted on the total variable costs, total fixed costs, total costs, the calculation of receipts, income calculation. Economic analysis in this study dilakuukan with: analysis of R/C, ROI analysis and profitability ratios. Meanwhile, to determine the effectiveness of the program FFS can be calculated by using the method of analysis Ginting. The results obtained from the analysis results Ginting that the program SLPHT effective, the results of economic analysis how rice cultivation is to observe the principles of IPM benefit the most from the way rice cultivation non IPM and behavioral changes of farmers who took SLPHT in view of the economic aspects as well as aspects technology.